MODERN CHALLENGES AND PROSPECTS IN HYDRAULIC ENGINEERING: AN INTEGRATIVE SCIENTIFIC REVIEW - Khalimov Ibrokhimjon (Journals Park Publishing, 2025)
This article presents an exhaustive, multidisciplinary review of modern hydraulic engineering within the global and regional context, focusing on the design, operation, and sustainability of hydraulic structures such as dams, canals, barrages, irrigation systems, and flood management facilities. The synthesis draws from contemporary research, international standards, and practice-based evidence to analyze technical advances, persistent operational challenges, and novel adaptation strategies in a rapidly changing environmental and socio-economic landscape. Particular emphasis is given to the interplay of hydrological variability, sediment transport, digitalization, aging infrastructure, climate adaptation, and ecosystem integration. The review includes extensive case studies from Uzbekistan and Central Asia, juxtaposed with global examples to provide a nuanced understanding of opportunities and barriers facing the sector. The article further discusses the integration of nature-based solutions, the role of stakeholder engagement, advances in digital monitoring, and the critical need for institutional and capacity development. Practical recommendations are provided to guide future hydraulic engineering research, education, and policy, advocating for systems thinking, resilience, and sustainability at every stage of project delivery and management.
Keywords: Hydraulic engineering; hydraulic structures; water resources; dams; canals; climate adaptation; sedimentation; ecohydraulics; digital water management; sustainable development.